Some 5-HT1A, 5-HT2A and 5-HT2C Receptor Ligands as Atypical Antipsychotic: In Silico Pharmacological Evaluation with ADME Predictions and Molecular Docking Techniques - Uslu, Harun (Society of Pharmaceutical Sciences of Ankara (FABAD), 2025)
Serotonin (5-HT) and its receptors are involved in various neuropsychiatric disorders, and altered serotoninergic neurotransmission and interactions between the 5-HT and dopamine (DA) systems contribute to the pathophysiology of psychotic disorders. Interactions with 5-HT receptors may contribute to the elucidation of the properties of modern antipsychotic drugs, whose long-term effects on 5-HT receptors have not yet been adequately evaluated. Many people in society show at least one of the symptoms of psychotic disorder, and the mortality rate is twice as high as that of a healthy person. In this study, we revealed the molecular docking results of some drug molecules defined as atypical antipsychotics on 5-HT1A, 5-HT2A, and 5-HT2C. We aimed to contribute to the development of new compounds that may be useful in the treatment of psychotic disorders by trying to demonstrate the relationship between their computational inhibitory activities and their structural properties. Docking study showed that Lurasidone (e) was one drug molecule with the best docking scores on the receptors. Also, it showed that Risperidone (h), Paliperidone (f), and Brexpiprazole (b) were one drug molecules withthe best pose on the receptors. Considering ADME predictions, all drug molecules (a-j) had good pharmacokinetic profiles, but Lurasidone was found to have some disadvantages. It seems that the use of Paliperidone and Risperidone may be more valuable, especially in the treatment of psychotic patients such as schizophrenia. © 2025 Society of Pharmaceutical Sciences of Ankara (FABAD). All rights reserved.
Atipik Antipsikotik Bazı 5-HT1A, 5-HT2A ve 5-HT2C Reseptör Ligandları: In Silico Farmakolojik Etkilerinin Moleküler YerleştirmeTeknikleriyleDeğerlendirilmesiveADMETahminleri
Keywords: 5-HT1A; 5-HT2A; 5-HT2C; ADME predictions; Atypical antipsychotics; molecular docking